Vulnerability assessment and feasibility analysis of seismic strengthening of school buildings - Chrysostomou, Christis; Kyriakides, Nicholas; Papanikolaou, V. K.; Kappos, A. J.; Dimitrakopoulos, E. G.; Giouvanidis, A. I. (My University, 2015)
The majority of structures in seismic-prone areas worldwide are structures that have been designed either without seismic design considerations, or using codes of practice that are seriously inadequate in the light of current seismic design principles. In Cyprus, after a series of earthquakes that occurred between 1995 and 1999, it was decided to carry out an unprecedented internationally seismic retrofitting of all school buildings, taking into account the sensitivity of the society towards these structures. In this paper representative school buildings are analysed in both their pristine condition and after applying retrofitting schemes typical of those implemented in the aforementioned large-scale strengthening programme. Non-linear analysis is conducted on calibrated analytical models of the selected buildings and fragility curves are derived for typical reinforced concrete and unreinforced masonry structures. These curves are then used to carry out a feasibility study, including both benefit-cost and life-cycle analysis, and evaluate the effectiveness of the strengthening programme.
Keywords: School buildings; Seismic vulnerability assessment; Non-linear dynamic analysis; Cost-benefit analysis; Life-cycle cost analysis